Reusing exterior wall framing systems: A cradle-to-cradle comparative life cycle assessment. (1st July 2019) - Cruz Rios, Fernanda; Grau, David; Chong, Wai K.
Highlights: Hybrid and process-based LCA generated opposite results. Hybrid LCA resulted in larger environmental benefits from reuse. Steel frame must be reused twice in order to produce lower impacts than wood frame. Benefits from reuse depended on reuse rates larger than 70%. Large transportation distances undermined the environmental gains of multiple reuses. Abstract: The construction industry consumes 40% of the global materials and produces one of the largest waste streams in the planet. In a circular economy, the reuse of building components in multiple life cycles aims at increasing resource efficiency and eliminating waste. But can reuse offset the environmental impacts of materials with high embodied energy (e.g. steel)? If so, in what conditions? In the study presented in this paper, the authors used two different life cycle assessment (LCA) methods to compare a single-use wood-framed wall against a reusable steel-framed wall in a tiny house in the U.S. The analyzed impact categories were global warming potential, embodied energy, and water use. One of the main goals of this study was to understand the benefits of reusing a material with high embodied energy when compared to a single-use alternative. Another equally important objective was to understand how different LCA methods can influence the results in a cradle-to-cradle (C2C) LCA. As results, reuse benefits depended on aggressive reuse rates (>70%) and multiple reuses of steel were needed to offset the embodied environmental impacts during steel production. Also, the analyses showed that process-based LCA and hybrid LCA can generate conflicting results in a C2C LCA.